(untitled) (Sinología hispánica. China Studies Review, 2018)
For the native speaker, the pause is an essential part of oral communication and has several functions such as indicating the turns between interlocutors, specifying the meaning in an ambiguous expression or marking the phonic or syntactical boundaries. However, inforeigner´s spontaneous discourse the pause is, otherwise, a sign of non-fluency which usually indicates cognitive problems. Based on Levelt’s "Speaking" Model, the present article aims to find out the cognitive problems of the Spanish-speaking students of intermediate and advanced level of Chinese in spontaneous discourse through analyzing the characteristics manifested in the production of pauses. The results show that advanced students have fewer breaks than mid-level students; the total duration of breaks is shorter; the average length of speech is longer and the average of speed is longer. But there is still distance to reach the natives in the mentioned parameters. In addition, those results of the distribution of the breaks reveal that the middle level students pay much attention to the formulation and articulation of short sentences while the advanced ones face problems in the organization of long sentences and therefore they must also pay attention to the self-monitoring.